Mechanism of Qingchang compound against coccidiosis based on network pharmacology-molecular docking - Yan, Zhiqiang; Chen, Chunlin; Zhai, Shaoqin; Tang, Hongmei; Zhu, Maixun; Yu, Yuandi; Zheng, Hua (Frontiers in Veterinary Science, 2024)
The aim of this study was to investigate the anti-Eimeria tenella mechanism of Qingchang Compound (QCC) and provide a basis for its clinical application. The active ingredients, active ingredient-disease intersection targets, and possible pathways of QCC for the treatment of chicken coccidiosis were analyzed, the binding ability of pharmacodynamic components and target proteins was determined by network pharmacology and the molecular docking, and a model of infection with coccidiosis was constructed to verify and analyze the mechanism of action of QCC against coccidiosis. Among the 57 components that met the screening conditions, the main bioactive components were quercetin, dichroine, and artemisinin, with IL-1β, IL-6, IL-10, IFN-γ, and IL-8 as the core targets. Simultaneously, the KEGG signaling pathway of QCC anti-coccidiosis in chickens was enriched, including cytokine-cytokine receptor interactions. The results showed that the main pharmacodynamic components of QCC and the core targets could bind well; artemisinin and alpine possessed the largest negative binding energies and presented the most stable binding states. In addition, in vivo studies showed that QCC reduced blood stool in chickens with coccidiosis, restored cecal injury, and significantly reduced the mRNA and protein expression levels of IL-1β, IL-10, and IFN-γ in ceca (P<0.01). Our results suggest that the main active ingredients of QCC are artemisinin and alpine and its mechanism of action against coccidiosis may be related to the reduction of the inflammatory response by acting on specific cytokines.